2011
DOI: 10.7205/milmed-d-d1-000141
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health-Promoting Behaviors in Military Spouses During Deployment Separation

Abstract: The purpose of this research was to describe predictors of participation in health-promoting behaviors among military spouses. A total of 105 female spouses of currently deployed active duty military members were surveyed to determine their perceived stress and participation in the health-promoting behaviors of exercise, diet, checkups, substance use/avoidance, social behaviors, stress management/rest, and safety/environmental behaviors. Demographic and deployment information was also collected. Regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Other limitations of this major project arose from the methodology. In keeping with previous research studies (Green et al, 2013;Padden et al, 2011;Joseph & Afifi, 2010), men were excluded from the study participants. With the recent advent of woman in combat roles, more male spouses may find themselves in a similar set of circumstances that had once been reserved for female military spouses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other limitations of this major project arose from the methodology. In keeping with previous research studies (Green et al, 2013;Padden et al, 2011;Joseph & Afifi, 2010), men were excluded from the study participants. With the recent advent of woman in combat roles, more male spouses may find themselves in a similar set of circumstances that had once been reserved for female military spouses.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Perceived Stress Scale, researchers found that stress was marginally increased during a spouse's deployment as compared to a normative sample of American woman. Military spouses appeared to feel their stress levels were not insurmountable; sixty percent of spouses studied denied feeling that stressors were insurmountable (Padden et al, 2011).…”
Section: Physical Health Of Military Spousesmentioning
confidence: 93%
“…Although most military spouses successfully cope with their additional responsibilities during deployment (Lester et al, 2010), research has documented elevated rates of depression, anxiety, and sleep problems among military spouses during deployment (Burton, Farley, & Rhea, 2009;Green, Nurius, & Lester, 2013;Mansfield et al, 2010). Lengthy deployments are also related to decreases in spousal participation in health-promoting behaviors, such as healthy diet and adequate rest (Padden, Connors, & Agazio, 2011).…”
Section: Stressors and Supports For Military Spousesmentioning
confidence: 98%
“…Studies comparing the mental health of military spouses/partners to women in the general population are also scarce, making it difficult to determine if there are additional or particular needs in this population. Those that have been conducted suggest significantly higher depression and PTSD among US and Australian spouses/partners compared to community samples, although similar levels of alcohol use (Alessi, Ray, Ray, & Stewart, 2001;Lester et al, 2010;O'Toole et al, 2010;Padden, Connors, & Agazio, 2011;Westerink & Giarratano, 1999).…”
Section: Introductionmentioning
confidence: 98%